Riparian vegetation of ephemeral streams. (March 2017) - Stromberg, Juliet C.; Setaro, Danika L.; Gallo, Erika L.; Lohse, Kathleen A.; Meixner, Thomas
Abstract: Ephemeral streams are abundant in drylands, yet we know little about how their vegetation differs from surrounding terrestrial zones and about their projected response to regional warming and drying. We assessed plant communities at seven ephemeral streams (and terrestrial zones) distributed among three climatic settings in Arizona. Compared to terrestrial zones, riparian zones had similar herbaceous cover but greater woody vegetation volume. They supported more plant species, with several woody taxa restricted to the ephemeral zone (consistent with the idea that herbaceous plants are rain-dependent while riparian trees rely on runoff stored in stream sediments). Their herbaceous communities had high compositional overlap with terrestrial zones and may sustain regional diversity as droughts intensify. Presumably owing to periodic flood disturbance, riparian plant communities had greater evenness than terrestrial zones, many of which were dominated by Eragrostis lehmanniana . Patterns along the climatic gradient suggest that increasing aridity will reduce the number of herbaceous (and total) plant species within riparian zones (110 species per stream in semihumid settings, 88 in semiarid, 48 in arid) and drive compositional shifts from perennials grasses and forbs to annuals. Hotter and drier conditions will drive sharp declines in herbaceous cover, converting riparian savanna to xeroriparian scrubland. Highlights: Ephemeral streams are the most abundant stream type in the American Southwest. Their riparian zones have more woody plant biomass, but similar herbaceous cover, than terrestrial zones. Ephemeral stream riparian zones support more plant species than terrestrial zones. Increasing aridity will reduce herbaceous species richness and cover and favor annuals over perennials. Increasing aridity will convert riparian savannah to xeroriparian scrubland.